Manajemen Risiko Keselamatan Dan Kesehatan Kerja Pada Instalasi Laundry Rumah Sakit Umum Daerah Ragab Begawe Caram Kabupaten Mesuji Tahun 2025 (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The hospital laundry installation is a non-medical supporting unit with a high risk of occupational health and safety (OHS) hazards due to direct exposure to chemicals, machinery, and contaminated linen. Potential hazards in this unit include physical (heat, noise), chemical (detergents and disinfectants), biological (viruses and bacteria from linen), and ergonomic (improper working posture) risks. This study is a descriptive quantitative research with a semi-quantitative approach. The aim is to identify, assess, evaluate, and control OHS risks in the laundry unit. Data were collected through observation, interviews, and document review with seven laundry staff members. Risk assessment was conducted using a risk matrix based on the AS/NZS 4360:2004 standard. The results show that several risks ranged from low to very high levels, including infection from linen, chemical exposure, noise, and injury from machinery. Risk control measures implemented include applying the hierarchy of controls, starting from elimination, substitution, engineering controls, Administratif controls, and the use of personal protective equipment (PPE). It is concluded that improvements in supervision, staff training, and facility upgrades are necessary to minimize occupational accidents in the laundry installation.